A Review: Divergent Emerging Strategies to Tackle Challenging Covid-19 - Puri, Sudha Unmesh; Bhimanwar, Arti Akash; Vaidya, Mrunal Mukesh (Journal of Drug Delivery and Therapeutics, 2020)
Background: Contemplating the severity of pandemic sequel for public health many researchers are working recklessly for new targeted drugs and vaccines. Despite the challenging opportunities, the setup for the development of new effective remedy against COVID-19 is unforeseeable. Objective: The aim of the present review was to explore the work done by some authors to battle against COVID-19. Material & Method: We analysed 24 articles from Elsevier and one from J Med virology journals stating different strategies to cope with this recently arrived monster COVID-19. Further are some targeting therapies viz., Niclosamide, immune response generated by cytotoxic T-cells and Natural Killer cells, Chloroquine and Hydroxy Chloroquine, blockade of Interleukin17, N- Acetylcysteine, mucolytic agents, oxytocin, bioflavonoids, triterpenoid saponins, ACE inhibitors or AII receptor antagonists, Hyperbaric oxygen therapy, serum albumin, Ritonavir, Tocilizumab, Furin, Amantadine, pioglitazone, Dapsone and doxycycline, steroids, plasama therapy, routine childhood immunization, a data-driven hypothesis on the epigenetic dysregulation of host metabolism by SARS corona viral infection, lipid metabolism has been proposed as a treatment target for COVID-19, COVIDiagnosis-Net proposed network for quick and accurate diagnosis. Result: We got to know how the people are struggling to find a cure for this pandemic affair. Conclusion: Till date, there is no specific treatment that has been confirmed to the effect against COVID-19. Let’s hope for the best. Key words: COVID-19, Novel Corona Virus Infection-2019, SARS-CoV2, Plasma therapy, Immunomodulators